A comparative study on the relative abrasiveness of locally available dentifrices - Guerrero, Ma. Carla S.; Rebong, Rowena B.; Medina, Vicente (Adviser).
Dentifrices are usually promoted for their flouride content but little is known about the abrasive agent. Abrasivity is desirable (within limits) to remove adherent deposits from the teeth. This study aimed to determine the degree of abrasivity of ten locally available dentifrices. The radiotracer technique was used. Radioactive specimen of human teeth were subjected to standardized brushing procedure invitro using a low speed micromotor. Abrasivity was determined with the Geiger Muhler counting machine by measuring the amount of radioisotope abraded against the the radioactive level of the control abrasive pumice. Results were analyzed using the ANOVA test. Ranking was done using the Duncan's New Multiple Range Test and revealed the least abrasive to the most abrasive as Pepsodent, Close-Up, Alert, Beam, Colgate, Hapee, Tawas, Exceed, Family and Maxam. The findings proved that there is a difference in the degree of abrasiveness of locally available dentifrices.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Dentifrices